2021
DOI: 10.1111/ijcp.14611
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a high visceral adiposity index on female sexual dysfunction in sexually active women? Results of a cross‐sectional study

Abstract: Aims To our knowledge, this is the first study investigating the impact of high visceral adiposity index (VAI) on female sexual dysfunction (FSD). We aimed to show the impact of increased levels of VAI on FSD compared with body mass index (BMI) and waist circumference (WC) particularly in those with metabolic syndrome (MeTS). Methods We included 158 participants in two groups: Group 1 (n = 68 with normal sexual function) and Group 2 (n = 90 with sexual dysfunction). Demographic, clinic data, presence of MeTS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Furthermore, a large cohort study from Beijing, China, suggested that VAI was an independent risk factor for diabetic nephropathy in the Chinese population ( 12 ). In addition, a considerable body of research has shown that higher VAI is positively associated with female sexual dysfunction ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a large cohort study from Beijing, China, suggested that VAI was an independent risk factor for diabetic nephropathy in the Chinese population ( 12 ). In addition, a considerable body of research has shown that higher VAI is positively associated with female sexual dysfunction ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%